Human rights, modernity and culture: understanding the position of lobola as a form of VAW and the current human rights normative standards and discourse on VAW - Mubaiwa, Pretty (Department of Public Law, 2022)
As the feminist movement in Africa continues to question and dismantle long-held religious and cultural beliefs and practices, this has influenced critical debates on the validity of their co-existence with human rights norms and standards on violence against women and discrimination. This dissertation aims to critically interrogate the relationship between culture, violence against women (VAW), and women's rights in Africa. Specifically, it delves into the cultural practice of bride price (also known as Lobola) to understand whether the practice is a cause and/or consequence of VAW in family relations. This dissertation hypothesises that Lobola is both a cause and consequence of VAW and should be explicitly identified as a form of VAW, a human rights violation. This dissertation adopts a theoretical analysis using Heise's Integrated Ecological Framework (Heise's framework) on VAW, which provides a valuable tool to analyse and deconstruct the systemic causes and influences of VAW. Heise's framework is adopted to analyse how certain cultural practices at the macro systemic level may relate to and influence VAW practices. To conduct this analysis using Heise's framework, this dissertation uses available literature on previously conducted focus group discussions on experiences, opinions and perceptions of Lobola by both young people and adults. The theoretical analysis highlights a positive correlation between Lobola and the violence women face in marriage and upon divorce. However, the research also establishes that the practice of Lobola itself does not present as a form of violence against women - but because of the perceptions, beliefs, and power systems it creates, the practice becomes an aggravator of VAW. The results from the analysis show that Lobola creates rigid gender roles, skewed beliefs of entitlement and ownership of women's lives and bodies, and asymmetrical power relations that influence VAW. Since the theoretical analysis proved that Lobola aggravates the violence women face in marriage and upon divorce, the dissertation also carries out a legal analysis to understand the position of harmful practices and the legal consequences using international human rights norms and standards on women's rights and VAW. In line with fulfilling its mandate, the United Nations Committee on the Elimination of all Forms of Discrimination against Women (CEDAW Committee), after receiving four state periodic reports from Kenya, Zambia, Zimbabwe and Uganda between 2010 and 2012, in its concluding observations expressed MBWPRE001-Pretty Mubaiwa concern over the persistence of harmful traditional and cultural practices that affect women. In each instance, the Committee reiterated that Lobola is a harmful practice that aggravates discrimination against women. These concluding observations ushered in an expanded narrative on harmful traditional and cultural practices that disproportionately affect women and thus promote gender-based discrimination. Using these four case studies, this dissertation, therefore, looks at these countries' customary and civil laws to understand the legislative landscape around traditional and cultural practices. The findings include that in all four states, Lobola is required to recognise and register a customary marriage. This means that legally, Lobola is recognised as a legitimate requirement for a marriage to be recognised and registered. Additionally, an appraisal of the standard-setting frameworks protecting the right of women to be free from violence and discrimination shows that, even though there are legally binding standards and mechanisms at the regional and international levels that are mandated to protect these rights, there are normative gaps that continue to impact the protection of women from violence negatively. The CEDAW Committee has called Lobola a harmful practice. However, as the principal women's rights body within the UN system, the Committee has failed to take further steps towards standard-setting or follow-up with states to continue encouraging the elimination of this practice. This gap limits the scope for women to pursue justice when they experience multiple and intersecting forms of violence in general. This dissertation thus concludes that Lobola should be specifically recognised as a form of VAW within the realm of harmful traditional practice. It is inconsistent with the current international standards on equality, non-discrimination, and violence against women.